In situ synthesis of metal (Bi0)-semiconductor [BiOX (X = Cl, Br, and I)] nanocomposites as a highly effective catalyst for the reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (New Journal of Chemistry, 2024)
The reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) has been efficiently catalyzed by in situ generated Bi-0-BiOX (X = Cl, Br, I) nanocomposites in the presence of sodium borohydride (NaBH4). The hierarchical 3D arrays of precursors (BiOCl, BiOBr, and BiOI) have been synthesized by a facile co-precipitation method at ambient temperature. The metallic Bi-0 is generated in situ by partial reduction of the Bi3+ ions in BiOX (X = Cl, Br, and I) mediated by NaBH4 during the conversion of 4-NP to 4-AP. In situ generated Bi-0-BiOX shows better catalytic activity than Bi-0-BiOX composite formed by mixing individually synthesized metallic Bi-0 particles with semiconducting BiOX nanoparticles. The Bi-0-BiOI nanocomposite demonstrated higher catalytic activity (k(app) = 0.529 min(-1)) compared to Bi-0-BiOCl (k(app) = 0.095 min(-1)) and Bi-0-BiOBr (k(app) = 0.098 min(-1)) due to its efficient conversion into metallic Bi-0. The approximate percentage composition of in situ generated metallic Bi-0 on the surface of BiOCl, BiOBr, and BiOI is nearly 10, 17, and 25%, respectively. Further, the reduction of 4-NP has been completed within 24, 22, and 6 minutes by in situ generated Bi-0-BiOCl, Bi-0-BiOBr, and Bi-0-BiOI nanocomposites from BiOCl, BiOBr, and BiOI, respectively. Extensive studies have been conducted to generate a better understanding of the actual catalytic sites present on the surface of the catalysts.

An in-depth study of the Fe-Se system at the nanoscale reveals remarkable results on the electrocatalytic oxygen evolution reaction - Singh, Dinesh; Ghalawat, Monika; Poddar, Pankaj (European Journal of Inorganic Chemistry, 2025)
A catalyst for an electrocatalytic oxygen evolution reaction (OER) is a key component of the large-scale storage of renewable energy through the conversion of water into oxygen and hydrogen. Iron-based selenide materials are currently being considered as potential options for electrocatalytic oxygen evolution reaction (OER) because of their, widespread availability, low cost, and outstanding performance. In this study, we employed a thermal decomposition method to synthesize all stable phases of the Fe-Se system, including Fe7Se8, Fe3Se4, FeSe2, and FeSe. Additionally, we slurry-coated these phases onto a three-dimensional (3D) nickel foam substrate. The prepared 3D electrodes of Fe7Se8, Fe3Se4, FeSe2, and FeSe exhibit remarkably low overpotentials of 270, 276, 299, and 289 mV at a current density of 50 mA/cm2 for OER. In addition, the catalytic activity for OER is also tested on glassy carbon electrodes to compare its performance with the Ni-foam 3D substrate. The Fe7Se8 phase in the Fe-Se system exhibits the highest catalytic activity towards OER on both substrates due to variations in the Fe2+/Fe3+ ratio and the presence of Fe vacancies (cation vacancies) within the crystal lattice. Moreover, a faradaic efficiency of 98 % was exhibited by Fe7Se8 for the oxygen evolution reaction (OER).
Keywords: Iron selenide system; OER electrocatalyst; Thermal decomposition method